Incidencia del clima organizacional en el desempeño laboral de la asistente ejecutiva y analista administrativo de la Universidad Técnica de Cotopaxi, sede la matriz, periodo 2022 - Atavallo Pullopaxi, Evelin Mishell (2022)
The organizational climate in public institutions such as the Technical University of Cotopaxi, has taken on great importance, because it seeks to determine its incidence in the work performance of each one of those who make up this institution, being that it is closely linked with the motivational factors in their work environment. The objective of the research is to determine the incidence in the organizational climate of the work performance of the collaborators, for which dimensions such as interpersonal relationships (fellowship and collaboration), interpersonal relationships (communication), group cohesion (teamwork) ), Quality of Work Life (well-being and physical health), Quality of Work Life (working conditions) Motivation (job satisfaction), Policies and Regulations (rights and obligations), which are fundamental pillars for the institution. The investigative method to apply is from the non-experimental quantitative research approach with the descriptive level, which used the survey technique and whose endorsed instrument was the measurement of the organizational climate of the authors V. Aiken and Alfa Cronbach also worked with the evaluation of job performance with indicators that measure their performance at work. The population under study was 17 people, such as: executive assistants and administrative analysts. The result obtained from this study is a correlation coefficient that is considered a positive relationship, this means that the organizational climate variables in job performance are directly and indirectly related. The research generated in the Technical University of Cotopaxi, a technical impact from the present, an instrument will be available that allows it to take into account the organizational climate. Regarding the perception of the organizational climate, it can be observed that the collaborators maintain an adequate climate within the executive assistant and administrative analyst area, take into account the given strategies, among which were already established in the given proposal, thus satisfactorily applying the proposed strategies. , since its success depends on this.